Performance evaluation of optimum combining for mobile communications with co-channel interference - Saikumar, Shruti. (2014)
In today's world, mobile communication has become absolutely indispensable and plays a pivotal role in our everyday lives. In this dissertation, various diversity combining techniques for Rayleigh, Rician and Nakagami-m channels for coherent (BPSK) and non-coherent (BFSK) reception are studied. There are limitations imposed on the quality of mobile communications by multipath fading and cochannel interference. Diversity combining techniques help in mitigating the problem of fading effectively. Further, to make it more efficient, statistical behaviour of the fading channel is exploited. The combining techniques considered are selection combining (SC), equal gain combing (EOC), maximal ratio combining (MRC) and a generalization of SC, where the two signals with largest amplitude are combined, which is called second- order selection combining or SC2. All the simulations are performed on MATLAB. Bit Error Rate (BER) curves are obtained from the simulation. The simulation results are used to compare the performance of the above mentioned combining techniques.